Coconut Scale Aspidiotus destructor Signoret (Insecta: Hemiptera: Diaspididae) - Salahud Din; Steven Arthurs (EDIS, 2015)
This document provides a comprehensive overview of the coconut scale (Aspidiotus destructor), detailing its distribution, description, life cycle, and economic impact. It highlights the pest’s global presence in tropical and subtropical regions, its distinctive physical characteristics, and its rapid reproduction cycle. The document also discusses the coconut scale’s host plants, including coconut, mango, and banana, and the damage it causes. Additionally, it outlines various management strategies, such as biological control using parasitoids and predators, cultural practices, and chemical treatments to mitigate infestations.